The Semiotics of Test Design: Conceptual Framework on Optimal Item Features in Educational Assessment Across Cultural Groups, Countries, and Languages - Solano-Flores, Guillermo (Frontiers in Education, 2021)
This paper offers a conceptual framework on test design from the perspective of social semiotics. Items are defined as arrangements of features intended to represent information, convey meaning, and capture information on the examinees’ knowledge or skills on a given content. The conceptual framework offers a typology of semiotic resources used to create items and discusses item representational complexity—the multiple ways in which the semiotic resources of an item are related to each other—and item semiotic alignment—the extent to which examinees share cultural experience encoded by items. Since the ability to make sense of items is shaped by the examinees’ level of familiarity with the social conventions underlying the ways in which information is represented, unnecessary representational complexity and limited semiotic alignment may increase extraneous item cognitive load and adversely impact the performance of examinees from certain populations. Semiotic test design allows specification of optimal pools of semiotic resources to be used in creating items with the intent to minimize representational complexity and maximize semiotic alignment for the maximum number of individuals in diverse populations of examinees. These pools of semiotic resources need to be specific to the content assessed, the characteristics of the populations of examinees, the languages involved, etc., and determined based on information produced by cross-cultural frequency analyses, cognitive interviews, focus groups, and expert panels.